2013
DOI: 10.1097/phh.0b013e3182550a83
|View full text |Cite
|
Sign up to set email alerts
|

HIV Status Determination Among Tuberculosis Patients From California During 2008

Abstract: Context-Human immunodeficiency virus (HIV) infection complicates care and contributes to poor outcomes among tuberculosis (TB) patients. The Centers for Disease Control and Prevention recommends that providers test all TB patients for HIV.Objective-We assessed completeness of HIV status determination among TB patients and identified key gaps in adherence.Design-We conducted a retrospective review of public health charts to determine the HIV status for all TB patients reported in California during 2008. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…Our findings are consistent with evidence showing that patients in public health TB clinics are more likely to receive care recommended in TB control guidelines. [25] – [31] Similar findings have been published in which clinicians and clinics with the most experience and volume provide care resulting in better outcomes to patients for other diagnoses such as HIV [32] and Staphylococcus aureus bacteremia. [33] – [35] The results also highlight the concept that public health TB clinics and programs warrant consideration as expert, specialty referral clinics, and not simply government sector safety net providers.…”
Section: Discussionsupporting
confidence: 54%
“…Our findings are consistent with evidence showing that patients in public health TB clinics are more likely to receive care recommended in TB control guidelines. [25] – [31] Similar findings have been published in which clinicians and clinics with the most experience and volume provide care resulting in better outcomes to patients for other diagnoses such as HIV [32] and Staphylococcus aureus bacteremia. [33] – [35] The results also highlight the concept that public health TB clinics and programs warrant consideration as expert, specialty referral clinics, and not simply government sector safety net providers.…”
Section: Discussionsupporting
confidence: 54%
“…[7] Although the type of TB medical provider (public vs. private) has been implicated in the failure to adhere to other clinical guidelines for the diagnosis and treatment of TB, the potential association between a patient’s provider type and specific poor HIV testing outcomes (failure of a provider to offer a test, patient refusal of a test) has not been examined in the ART era. [1417, 21] This study framed the issue of HIV testing and TB providers within the high TB and HIV incidence area of NYC, focusing on the ART era (2001–2007).…”
Section: Discussionmentioning
confidence: 99%
“…[11] Recent data exploring the relationship between the type of TB medical provider and adherence to HIV testing recommendations are predominately descriptive and did not differentiate a provider’s failure to offer an HIV test and a patient’s test refusal. [21]…”
Section: Introductionmentioning
confidence: 99%
“…The results of our review suggest a need for updated estimates of the costs of TB hospitalization because TB hospitalization practices may have changed since then. A study of human immunodeficiency virus (HIV) testing of TB case patients in California in 2008 suggested that as few as one-third of TB patients were hospitalized [ 9 ], compared to one half of patients in the mid-1990s [ 10 ]. On the other hand, a study of 135 MDR TB patients in the US during 2005–2007 demonstrated longer times in the hospital, and increased drug resistance, which cost more, compared to study cohorts from a 1996 study [ 11 ].…”
Section: Discussionmentioning
confidence: 99%